نمذجة الآلات الكهربائية باستخدام Matlab And Simulink - محمود, علي أحمد (Latakia University Journal -Engineering Sciences Series, 2019)
إنّ استخدام الكمبيوتر في العملية التدريسية أضحى من الوسائل التعليمية التي تحقق مردودية عالية من حيث إيصال المعلومة بسهولة إلى ذهن الطالب كما أنها تحقق تقديم أكبر كمية من المعلومات في نفس الفترة الزمنية مقارنة بالطريقة الكلاسيكية للمحاضرة. من أجل تحقيق هذا الهدف لابد من صياغة المادة العلمية بطريقة يمكن عرضها من خلال الكمبيوتر ويتيح مناقشتها ودراسة النتائج والحالات المختلفة لعمل الآلة. في هذا العمل محاولة لصياغة طريقة لتدريس الجانب العملي لمقرر الآلات الكهربائية وذلك باستخدام النمذجة الرسومية بمساعدة برنامج Matlab & Simulink . هذه الطريقة ستتيح للطالب التعرف على: 1 - التجربة ومكوناتها والنتائج المتوقعة منها قبل إجرائها في المختبر. 2 – فهم التجربة واستيعاب المقرر. Using computer in the instructional process became one of the educational instruments, which provide high productivity in delivering information easily to the student. It also concludes the production of the highest quantity of information in the same period of the time compared with the traditional way of lecturing. To conclude this aim, the scientific material must be formed in a way that can be presented through the computer and give the chance to discuss and study the different results of how the machine works. The research tries to formulate a way to study the practical side of the electrical machines subject using sketching samples with the help of the Matlab and Simulink program. This way will give the student the chance to be acquainted with this experiment and its components as well as the expected results before concluding it in the laboratory. It will help students to understand the experiment and increase clearly the possibility of understanding the course.